Akses air bersih di pesisir Jakarta terhadap kesehatan dan kesejahteraan masyarakat - Ridwan, Nur Muthi’ah Rezkiyanti; Afla, Rohadatul Aisy; Rizki, Rakhmawati; Suryanegara, Ellen (Waste Handling and Environmental Monitoring, 2024)
This paper analyze inqeuality of access to clean water in Penjaringan District which is in coastal area in DKI Jakarta and its impact on health and welfare on people in coastal areas. The existing problem is community daily activities using groundwater as the primary source for daily water needs, causing land subsidence and seawater intrusion into groundwater, hence the decline on the groundwater’s quality and consequently it cannot be used to meet community’s water demand. Qualitative approach is used in this paper. The main analysis method used is analytical descriptive methods. The results obtained shows that there is a shortage of clean water in the community in Penjaringan District, and to meet their daily water needs, only 60,10% of people in Penjaringan District were able to get access of clean water from government’s water supply companies, and the other 38,79% people chose to buy water from another parties. The impacts are seen on the low welfare in the poor community side. Another impact is the minimum standard for health services in Penjaringan Districts still hasnt been fulfilled yet hence it can affect health services available in that district. It can be concluded that there are an imbalance of meeting community demand for clean water in Penjaringan District and it has impacts on the health and welafer of the community.